Rapid effectiveness of certolizumab pegol in non-radiographic axial spondyloarthritis - A. Spadaro; A. Scarno; A. Carboni; F.M. Perrotta; C. Catalano; E. Lubrano; G. Valesini (PAGEPress Publications, 2013)
In axial spondyloarthritis (SpA), the efficacy of certolizumab pegol (CZP), a novel pegylated anti-tumor necrosis factor alpha drug has not been investigated. We report that CZP showed a rapid effectiveness, assessed clinically and by magnetic resonance imaging, in a patient with a non-radiographic axial SpA, classified according to Assessment in SpondyloArthritis International Society (ASAS) criteria. This case suggests that CZP could be considered an useful treatment in non-radiographic axial SpA, supporting that an earlier therapeutic approach could play a relevant role in the management of the disease.